Dinamika Pembentukkan Calon Katekis dalam Menghadapi Tantangan Kecerdasan Buatan di STP IPI Malang - Fabiana Christa Natalia; Monica Innanda Chiaralazzo; Intansakti Pius X (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
. The rapid development of artificial intelligence (AI) has brought significant changes in various fields, including education and church life. This study aims to examine the dynamics of the formation of prospective catechists in facing the challenges of AI use at the IPI Malang Pastoral College. This study used a qualitative, descriptive approach, through observation and interviews with students as research subjects. The results show that the use of AI has become an integral part of the learning process, helping students understand material, develop academic skills, and enhance creativity in the pastoral field. However, the use of AI also poses challenges in the form of a tendency towards instantaneous attitudes and potential dependency that can hinder critical thinking skills and deep reflection on faith. In the context of pastoral education, the formation of prospective catechists emphasizes not only intellectual aspects but also spirituality, personality, and pastoral sensitivity. Therefore, the wise and proportional use of AI is necessary, while still positioning it as a supporting tool, not a substitute for human roles. The role of lecturers and educational institutions is crucial in guiding students to be able to use technology critically, reflectively, and responsibly. Thus, the integration of technology and faith values ​​is expected to produce prospective catechists who are able to respond to the challenges of the times in a relevant and meaningful manner.